Pathogens, density dependence and the coexistence of tropical trees. - Freckleton, R; Lewis, O (2006)
There is increasing interest in the role played by density-dependent mortality from natural enemies, particularly plant pathogens, in promoting the coexistence and diversity of tropical trees. Here, we review four issues in the analysis of pathogen-induced density dependence that have been overlooked or inadequately addressed. First, the methodology for detecting density dependence must be robust to potential biases. Observational studies, in particular, require a careful analysis to avoid biases generated by measurement error, and existing studies could be criticized on these grounds. Experimental studies manipulating plant density and pathogen incidence will often be preferable, or should be run in parallel. Second, the form of density dependence is not well understood and, in particular, there are no data indicating whether pathogens cause compensating or overcompensating density responses. Owing to this, we argue that the potential for pathogen-induced density dependence to generate diversity-enhancing outcomes, such as the Janzen-Connell effect, remains uncertain, as coexistence is far more probable if density dependence is overcompensating. Third, there have been few studies examining the relative importance of intra- or interspecific density dependence resulting from pathogens (or, more widely, natural enemies). This is essentially equivalent to asking to what extent pathogens are host-specific. If pathogens are generalists, then mortality rates will respond to overall plant density, irrespective of plant species identity. This will weaken the intraspecific density dependence and reduce the diversity-promoting effects of pathogens. Finally, we highlight the need for studies that integrate observations and experiments on pathogens and density dependence into the whole life cycle of trees, because as yet it is not possible to be certain of the degree to which pathogens contribute to observed dynamics.